Ethical issues in handling patients' information in electronic healthcare system / Sapiah Sulaiman - Sulaiman, Sapiah (2003)
This thesis focuses on analyzing the ethical issues in the hospitals that use manual system (Hospital Sultanah Aminah, Johor Bahru) and computerized system (Hospital Selayang, Selangor). The objective of this research is to identify the differences in handling or managing patients' information between these two hospitals. Questionnaires were distributed to the healthcare professionals who work in Surgical Wards in both hospitals. Furthermore, interview sessions were conducted on the staffs in IT Department and Medical Record Department to gain more information about the level of security information. On the whole, it can be said that 67% of the respondents in Hospital Sultanah Aminah perform their daily operations according to ethical guidelines compared to 58% at Hospital Selayang. Finally from this research an ethical framework will be derived which was improved from the Malaysian Medical Council code of professional conduct to adapt to the new situation. This research will help to identify the level of information of accessibility by usage of this information and to improve the safeguarding of the consumers' privacy in relationships with third parties. Hopefully, it will help to increase the patients' trust to the hospitals, and offer new experience in online health information and services to the patients.